Composition of Anura Species in Three Types of Habitats in Belaban Resort, Bukit Baka Bukit Raya National Park, West Kalimantan - Marisa, Utin; Junardi, Junardi; Saputra, Firman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Anura relies on habitats that are still preserved for its survival. The Bukit Baka Bukit Raya National Park offers natural and well-preserved habitats that support the survival of Anura. Data on the composition of Anura species are crucial for a conservation area, as the diversity of Anura is one of the parameters for maintaining the balance and sustainability of the ecosystem in the area and the environmental quality around it. However, there is no available data on the composition of Anura at Belaban Resort. This study aims to examine the composition of Anura in three habitat types at Belaban Resort, Bukit Baka Bukit Raya National Park. The method used in this study was a Visual Encounter Survey (VES) along the river at three locations, conducted from 18:00 to 22:00 WIB. The data obtained were analyzed descriptively, including the number of families, the number of species, the number of individuals, and environmental factors. The composition of Anura found consists of 13 species from 7 genera and 5 families, with a total of 234 individuals. The most commonly found family is Ranidae, and the most frequently encountered species is Fejervarya cancrivora, while the least numerous are Kalophrynus meizon and Leptobrachella hamidi. The conservation status of Meristogenys jerboa is vulnerable.